2001
DOI: 10.3758/bf03194439
|View full text |Cite
|
Sign up to set email alerts
|

Contextual influences on the internal structure of phonetic categories: A distinction between lexical status and speaking rate

Abstract: Previous research has shown that phonetic categories have a graded internal structure that is highly dependent on acoustic-phonetic contextual factors, such as speaking rate; these factors alter not only the location of phonetic category boundaries, but also the location of a category' s best exemplars. The purpose of the present investigation, which focused on the voiceless category as specified by voice onset time (VOT), was to determine whether a higher order linguistic contextual factor, lexical status, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 38 publications
1
29
1
Order By: Relevance
“…That is, the effect of the preceding context was larger in the cases of more ambiguous signals-the intermediate conditions of our Coda Signal series-than in cases of clear signals-the endpoints of our Coda-Signal series. This mirrors other findings on context effects in speech perception, which have also shown maximal context effects for ambiguous signals (Allen & Miller, 2001;Gow, 2003;Fowler et al, 2000;Liberman, 1996;Lotto & Kluender, 1998;Mann, 1980;Massaro & Cohen, 1983;Nittrouer & StuddertKennedy, 1987;Sinnott & Saporita, 2000).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…That is, the effect of the preceding context was larger in the cases of more ambiguous signals-the intermediate conditions of our Coda Signal series-than in cases of clear signals-the endpoints of our Coda-Signal series. This mirrors other findings on context effects in speech perception, which have also shown maximal context effects for ambiguous signals (Allen & Miller, 2001;Gow, 2003;Fowler et al, 2000;Liberman, 1996;Lotto & Kluender, 1998;Mann, 1980;Massaro & Cohen, 1983;Nittrouer & StuddertKennedy, 1987;Sinnott & Saporita, 2000).…”
Section: Resultssupporting
confidence: 65%
“…The same fricative noise is more likely to be perceived as an /s/ in the form /krIsm>/+fricative, in line with the word 'christmas', than in the form /fulI/+ fricative, which becomes the word 'foolish' if the fricative is interpreted as /P/ (see, e.g., McQueen, 1996, for a review). Such lexical context effects are, however, not mandatory (McQueen, 1991) and seem to have less of an impact on phonetic perception than phonetic context effects (Allen & Miller, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…None of the previously reported contextual effects (Allen & Miller, 2001;Diehl, Elman, & McCusker, 1978;Eimas & Corbit, 1973;Iverson & Kuhl, 2000; have been examined in terms of their temporal dynamics. Indeed, only some mathematical models of speech perception have tried to address changes in performance due to changes in ISI (e.g., Macmillan, Goldberg, & Braida, 1988;Schouten & van Hessen, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of context effects have been reported in the speech perception literature, such as adaptation effects (Eimas & Corbit, 1973), lexical effects (Allen & Miller, 2001), contrast effects (Diehl, Elman, & McCusker, 1978), and order effects (Lotto, Kluender, & Holt, 1998). Perhaps the best known is the perceptual magnet effect (Iverson & Kuhl, 1996;Kuhl, 1991Kuhl, , 1994, whose interpretation remains controversial (e.g., Lotto, Kluender, & Holt, 1998).…”
mentioning
confidence: 99%
“…Listeners take this into account and interpret durational cues relative to rate information in the surrounding context (see Miller, 1981Miller, , 1987 for overviews). The effect of rate, that is, the effect of a linear manipulation of the acoustic duration of segments adjacent to a target segment, has been investigated extensively in the domain of phoneme perception (e.g., Allen & Miller, 2001;Miller, 1981;1987;Miller & Dexter, 1988;Miller & Liberman, 1979;Miller & Wayland, 1993). Recently, it has also been demonstrated that rate modulates perception of duration as a suprasegmental lexical-stress cue (Reinisch, Jesse, & McQueen, in press).…”
mentioning
confidence: 99%